Inventory control: Its principles and application - Singh, Ankita; Rasania , Sanjeev Kumar; Barua, Kabita (Indian Journal of Community Health, 2022)
Availability of good quality stock, in right quantity, at right place and time and at right cost is the essence of inventory control, which in turn is mandatory for smooth functioning and service delivery of any health care facility. Various techniques are available for inventory control, based on cost, criticality and other factors for e.g., ABC analysis, VED analysis, ABC-VED matrix, FSN analysis, SDE analysis etc. Each technique has its own strength and weakness in its applicability. Economic considerations are also imperative for logistic management of any health facility, as any cost savings could be spent more gainfully in some other way and thus more lives could be saved, reduced morbidities and overall positive impact. Future healthcare managers will have to utilize scientific methods of inventory management and the role of an efficient hospital logistics system cannot be ignored anymore. Inventory control is an important component of hospital management. It provides significant improvement in patient care, customer relationships and optimal use of resources. The objective of this paper is to present an up-to-date review of inventory control and critically appraise its various techniques, various costs associated with it and methods of indenting stock. This review will benefit post-graduate students and public health workers in understanding the concepts and principle of inventory control and applying the same in their practice.